2009
DOI: 10.1063/1.3077610
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural improvements of InP on GaAs (001) grown by molecular beam epitaxy by in situ hydrogenation and postgrowth annealing

Abstract: Articles you may be interested inGrowth of InP on GaAs (001) by hydrogen-assisted low-temperature solid-source molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Morales et al [7] also showed direct growth of InP on on-axis GaAs (0 0 1) via molecular beam epitaxy (MBE) with a resulting threading dislocation density of 10 8 cm À 2 . These results are not surprising as direct growth of highly lattice-mismatched systems InP on GaAs, or GaAs on Si leads to large strains (4 3.5%) at the mismatched interface, which result in the nucleation of large quantities of dislocations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Morales et al [7] also showed direct growth of InP on on-axis GaAs (0 0 1) via molecular beam epitaxy (MBE) with a resulting threading dislocation density of 10 8 cm À 2 . These results are not surprising as direct growth of highly lattice-mismatched systems InP on GaAs, or GaAs on Si leads to large strains (4 3.5%) at the mismatched interface, which result in the nucleation of large quantities of dislocations.…”
Section: Introductionmentioning
confidence: 94%
“…Summary of threading dislocation density results for films up to InP lattice constant on GaAs substrate in the literature and this work[6][7][8][9]12].…”
mentioning
confidence: 96%
“…Misfit segments can lie along the []1true10 direction in the (001) growth plane, while threading segments rise up on the {111} plane in the same direction [6,25]. Threading dislocations on the {111} plane are a result of the planes' lower facet surface energy [13,14]. Threading dislocations make a 45° angle with the underlying Si (001) substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Threading segments originate from the GaAs/Si interface and rise to the {111} plane, making an angle with the fundamental Si(001) substrate [6,18]. Stacking faults and twins easily form on the preferred {111} plane due to it having the lowest surface facet energy and the largest plane spacing [19,20]. During the GaAs epitaxial growth procedure, some stacking faults for GaAs on Si multiply or self-annihilate.…”
Section: Resultsmentioning
confidence: 99%